The Relationship of Divergent Thinking Ability, Learning Discipline, and Resilience to Adversity Towards The Mathematics Learning Outcomes of 5th Grade Elemtary School Students in Cluster 2 Mekarsari-Baturiti: English - Mahayani, Ni Gusti Agung Made; Darmada , I Made; Adji , Sandra Sukmaning (Universitas Wiralodra, 2023)
This study aims to determine the relationship between divergent thinking ability, learning discipline, and resilience to adversity towards the mathematics learning outcomes of fifth-grade elementary school students in Cluster 2 Mekarsari-Baturiti. This research is correlational. The population in this study was 123 students, while the research samples were determined by using the Slovin formula and the obtained results were 94 students. Data collection methods used in this study were questionnaires, tests, and document studies. Data analysis used in this study is multiple regression and partial correlation. Based on the research that has been done, it can be concluded that: 1) There is a relationship between divergent thinking ability and mathematics learning outcomes of 5th grade elementary school students in Cluster 2 Mekarsari-Baturiti with a moderate correlation category. 2) There is a relationship between learning discipline and the mathematics learning outcomes of 5th grade elementary school students in Cluster 2 Mekarsari-Baturiti with a strong correlation category. 3) There is a relationship between resilience to adversity and the mathematics learning outcomes of 5th grade elementary school students in Cluster 2 Mekarsari-Baturiti with a very strong correlation category. 4) There is a simultaneous relationship between divergent thinking ability, learning discipline, and resilience to adversity on the mathematics learning outcomes of 5th grade elementary school students in Cluster 2 Mekarsari-Baturiti with a very strong correlation category.